Substance P and Calcitonin Gene-Related Peptide: Key Regulators of Cutaneous Microbiota Homeostasis - N’Diaye, Awa; Gannesen, Andrei; Borrel, Valérie; Maillot, Olivier; Enault, Jeremy; Racine, Pierre-Jean; Plakunov, Vladimir; Chevalier, Sylvie; Lesouhaitier, Olivier; Feuilloley, Marc G. J. (Frontiers in Endocrinology, 2017)
Neurohormones diffuse in sweat and epidermis leading skin bacterial microflora to be largely exposed to these host factors. Bacteria can sense a multitude of neurohormones but their role in skin homeostasis was only investigated recently. The first study focussed on Substance P (SP), a neuropeptide produced in abundance by skin nerve terminals. SP is without effect on the growth of Gram positive (Bacillus cereus, Staphylococcus aureus, Staphylococcus epidermidis) and Gram negative (Pseudomonas fluorescens) bacteria. However, SP is stimulating the virulence of Bacillus and Staphylococci. The action of SP is highly specific with a threshold below the nanomolar level. Mechanisms involved in the response to SP are different between bacteria although they are all leading to increased adhesion and/or virulence. The moonlighting protein EfTu was identified as the SP binding site in B. cereus and Staphylococci. In skin nerve terminals, SP is co-secreted with the Calcitonin-Gene-Related-Peptide (CGRP), which was shown to modulate the virulence of S. epidermidis. This effect is antagonized by SP. Identification of the CGRP sensor, DnaK, allowed understanding this phenomenon as EfTu and DnaK are apparently exported from the bacterium through a common system before acting as SP and CGRP sensors. Many other neuropeptides are expressed in skin and their potential effects on skin bacteria remain to be investigated. Integration of these host signals by the cutaneous microbiote now appears as a key parameter in skin homeostasis.